Yurtluk-Ocaklıks: land, politics of notables and society in Ottoman Kurdistan, 1820-1890 - Bayraktar, Uğur. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2015., 2015)
This dissertation examines the transformation of family estates (yurtluk-ocaklık and hükûmet) in Ottoman Kurdistan during the nineteenth century. Since these lands provided their possessors with political and economic privileges, this study also sheds light on the transformation of Kurdish emirs as yurtluk-ocaklık and hükûmet holders in their provincial setting. The Tanzimat period (1839-1876), in which the centralisation reforms accelerated, contravened the political and economic concessions associated with yurtluk-ocaklık lands. Following the case of yurtluk-ocaklık and hükûmet lands possessed by the Zirki emirs in northeastern Diyarbekir, this dissertation offers the contested concept(s) of property related with these lands and their fates in the aftermath of the Land Code of 1858. As the latter is usually associated with the genesis of modern private property in the Ottoman context, this dissertation contemplates contrasting perceptions with regards to private property beyond the definitions dictated by the Ottoman government. By doing so, this study scrutinizes the making of yurtlukocaklık and hükûmet lands as private property at the interstices of Zirki emirs and the Ottoman government. Demonstrating the complication nature underlying the making process, it also shows the process was not a straightforward one but rather included many participants with their own agendas. Accordingly, this study scrutinizes the changing notions of politics provincial notables conducted to which Zirki emirs belonged. With a focus on the commmercialisation of agriculture in the Ottoman realm from the middle of the century onwards, this dissertation attempts to show how land possession was related with economic-cum-political power throughout the nineteenth century in Ottoman Kurdistan.
Keywords: Kurds -- Turkey -- History -- 19th century.; Land tenure -- Law and legislation -- Turkey.; Land titles -- Registration and transfer -- Turkey.